Multiplexing midbrain neurons entrain movement dependent decision-making - Shin, Wooyeon; Paik, Se-Bum; Kim, Jeongjin (Cognitive Computational Neuroscience (CCN2024), 2024)
The brain can regulate decision-making by multiplexing information from the internal state and external context. Despite the importance of ongoing motor signals as an internal state, how the movement state dynamically updates the decision process is largely unknown. Here, we designed a novel perceptual decision-making task conducted on a treadmill to investigate the neural correlates associated with movement state-dependent decision-making. We focused on the neural activity of the mesencephalic locomotor region (MLR), a midbrain area involved in movement control. We uncovered that MLR encodes internal kinematic (walk, lick) and external context (reward, sensory stimulus) information concurrently at the single neuron level. In addition, we revealed that the subsets of these multiplexing MLR neurons encode modulation in decision-making associated with different movement states, primarily through alterations in the evidence accumulation phase. Collectively, these findings propose that the multiplexing of MLR neurons is a key regulator for state-dependent decision processes. Our findings will provide insight into the underlying mechanism of cognitive process during perceptual decision-making depending on the movement state.